2008
DOI: 10.1086/592733
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter Array Observations of Infrared Dark Clouds: A Tale of Two Cores

Abstract: We present high angular resolution submillimeter continuum images and molecular line spectra obtained with the Submillimeter Array toward two massive cores that lie within infrared dark clouds (IRDCs), one actively star-forming (G034.43+00.24 MM1) and the other more quiescent (G028.53À00.25 MM1). The high angular resolution submillimeter continuum image of G034.43+00.24 MM1 reveals a compact ($0.03 pc) and massive ($29 M ) structure, while the molecular line spectrum shows emission from numerous complex molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 29 publications
(63 reference statements)
7
92
0
Order By: Relevance
“…In the cores embedded within IRDCs observed by Rathborne et al (2007), three cold condensations are found with masses from 9 to 21 M and sizes ranging from 5200 to 8200 AU (0.026 and 0.041 pc). Rathborne et al (2008) discovered four additional condensations in two other IRDCs with masses ranging from 9 to 29 M but in a larger average size of 12 000 AU (0.06 pc). Zhang et al (2009) investigated G28.34+0.06 where 7 massive condensations were reported with masses ranging from 22 to 97 M inside physical sizes not provided in their article but which are probably significantly larger than the observation beam of 1.2 , which corresponds to 5800 AU.…”
Section: Envelope Masses Of the Proto-stellar Objectsmentioning
confidence: 98%
“…In the cores embedded within IRDCs observed by Rathborne et al (2007), three cold condensations are found with masses from 9 to 21 M and sizes ranging from 5200 to 8200 AU (0.026 and 0.041 pc). Rathborne et al (2008) discovered four additional condensations in two other IRDCs with masses ranging from 9 to 29 M but in a larger average size of 12 000 AU (0.06 pc). Zhang et al (2009) investigated G28.34+0.06 where 7 massive condensations were reported with masses ranging from 22 to 97 M inside physical sizes not provided in their article but which are probably significantly larger than the observation beam of 1.2 , which corresponds to 5800 AU.…”
Section: Envelope Masses Of the Proto-stellar Objectsmentioning
confidence: 98%
“…We stress here that the term IR-dark adopted by the authors we refer to is based on MSX observations, and that some sources in the IR-dark subsample may be detected at mid-IR wavelengths with more sensitive telescopes such as Spitzer. We are aware that at least some of our IR-dark sources are mid-IR emitters: G34.43+0.2M1 has a bolometric luminosity of 2 × 10 4 L (Rathborne et al 2008), and so does G24.60+0.1M2 (Rathborne et al 2007). However we keep our classification as it is, noting that this category of molecular clumps will perhaps need further sub-classifications as our knowledge on them improves.…”
Section: The Samplementioning
confidence: 99%
“…Such massive core studies require a resolution much higher than this study; they have to resolve the clumps into cores. Several studies on fragmentation were recently carried out using the Plateau du Bure or the SMA interferometers Rathborne et al 2007Rathborne et al , 2008Zhang et al 2009;Swift 2009). They show that the 1.2 mm clumps fragment into smaller cores, but cannot tell at what level the fragmentation halts.…”
Section: Comparison With Theoretical Modelsmentioning
confidence: 99%
“…A&A 515, A42 (2010) Massive stars generally form in clusters (Lada & Lada 2003), of which the precursors are massive clumps or the so-called precluster forming clumps, hereafter just clumps, of a ∼1 pc size. For many massive star-forming regions, we do not yet have the capacity to resolve the clumps into prestellar cores and study the fragmentation ; Rathborne et al 2007Rathborne et al , 2008Zhang et al 2009;Swift 2009). In this paper, we report on the physical parameters of the clumps, such as their morphology, density and temperature.…”
Section: Introductionmentioning
confidence: 99%